The Making of Modern Turkey : Nation and State in Eastern Anatolia, 1913-1950 - Üngör, Ugur Ümit (OUP Oxford, 2012)
The eastern provinces of the Ottoman Empire used to be a multi-ethnic region where Armenians, Kurds, Syriacs, Turks, and Arabs lived together in the same villages and cities. The disintegration of the Ottoman Empire and rise of the nation state violently altered this situation. Nationalist elites intervened in heterogeneous populations they identified as objects of knowledge, management, and change. These often violent processes of state formation destroyed historical regions andemptied multicultural cities, clearing the way for modern nation states. The Making of Modern Turkey highlights how.